Gouvernorat Kafr esch-Scheich, Ägypten. Landschaftsarchäologie und regionale Siedlungsnetzwerke um den Fundplatz Tell el-Faraʿin (Buto) im Nildelta. Die Arbeiten des Jahres 2016 - Schiestl, Robert (e-Forschungsberichte des DAI, 2017)
The archaeological survey in this northern part of the Nile delta has uncovered a dense network of predominantly Roman and Late Roman settlements. Work in 2016 continued on embedding these settlements in their ancient natural environment. The focus last season was on some very prominent natural features – long narrow raised ridges, running roughly North-South. The assumption that each of these features represented the remains of two alluvial levees, flanking a former Nile branch, could be verified by auger core drillings.